Effectiveness of Learning Methods Drill and Demonstration - Eko Purnomo; Eddy Marheni; Insonia Mardatilah (Performa, 2019)
Physical education is basically education through physical activities which are used as a medium to achieve overall individual development. This study aims to find appropriate and effective methods for obtaining learning outcomes. Researchers conducted observations at the SMA Development and SMK N5 Padang. The results of this study can be explained that the method used by high school development teachers in teaching PJOK is the method of ready training (drill) while the method used by teachers of SMK 5 Padang in teaching PJOK is a demonstration method. This difference is because each school has different teaching in conducting learning to each student included in PJOK lessons. In terms of effectiveness in learning, it is explained that each school and student characteristics have differences, so that some methods can only be applied to certain schools. In addition, in this study, there are basically differences between high school and vocational high school subjects